دراسة أثر التوزعات الاحتمالية لأزمنة توليد الرزم على عوامل جودة الخدمة في شبكات الـ MANET - حجازية محمد; عباس بشار (Latakia University Journal -Engineering Sciences Series, 2018)
Ad-hoc Networks is considered as the most commonly propagated networks in the few recent years, because of their structures that depends on many hosts communicating together without any pre-installed infra-structure such as servers and routers, each node of these introduce some services, besides of routing packages to neighbors according to the route included in the header of the transmitted package, MANETs Networks are considered as Ad-hoc Networks with the feature of mobility. Researchers recently have introduced many of routing protocols that works on MANET Networks, some of them store the routes from any node to any another node existing in the network into a table witch is updated periodically, this kind of protocols is known as Proactive Protocols, another kind of those protocols don’t store the routes in a such table because of the large size that a table reserved in a large networks, instead they request the route to the destination on-demand, and this kind is known as Reactive Protocols, the third type of protocols is Hybrid Protocols witch involve the two preceding schemes. We will study the effect of probability distribution of the packets generation periods on the QoS factors such as load, throughput, using one reactive protocol and one proactive protocol on three scenarios (25-75-200) nodes respectively. تعتبر شبكات الـAd-hoc من أكثر أنواع الشبكات انتشاراً في السنوات القليلة الماضية، ويرجع ذلك إلى بنية هذه الشبكات والتي تقوم على الاتصال بين العقد على أساس اللامركزية، ومن دون الحاجة إلى وجود أية بنى تحتية ثابتة مثل المخدمات والموجهات لأن خدمات الشبكة تكون موزعة على كل العقد بالإضافة إلى أن كل عقدة من عقد الشبكة تتولى عملية توجيه الرزم إلى كافة العقد المجاورة بناءً على مسار التوجيه المتضمن في ترويسة العقد المتنقلة عبر الشبكة، أما شبكات الـ MANET فهي عبارة عن شبكات Ad-hoc ولها نفس الميزات والخصائص باختلاف أن العقد تكون متنقلة. توصل الباحثون إلى عدد من أنواع البروتوكولات التي تعمل على شبكات الـ MANET، وتختلف هذه البروتوكولات بشكل عام في أسلوب توجيهها للرزم، فمنها ما يقوم على تخزين مسارات التوجيه من أية عقدة إلى أية عقدة أخرى موجودة في الشبكة ضمن جداول يتم تحديثها بشكل دوري وهذا ما يُعرف بالنوع التفاعلي Proactive، أما النوع الثاني فلا يعتمد على مثل هذه الجداول بسبب ازدياد حجمها مع ازدياد حجم الشبكة وإنما تعتمد هذه البروتوكولات على اكتشاف مسار التوجيه فقط عند الحاجة إليه ويُسمّى هذا النوع بالاستباقي Reactive، وهناك نوع ثالث وهو الهجين Hybrid حيث تجمع هذه البروتوكولات ميزات كلاً من النوعين السابقين. تم في هذا البحث دراسة أثر التوزع الاحتمالي لأزمنة توليد الرزم على عوامل جودة الخدمة مثل الحمل والمردود ومقارنة النتائج عند استخدام البروتوكولات التفاعلية والاستباقية في سيناريوهات تتضمن (25-75-200) عقدة على الترتيب.